2009
DOI: 10.15288/jsad.2009.70.543
|View full text |Cite
|
Sign up to set email alerts
|

Anxious Arousal and Anhedonic Depression Symptoms and the Frequency of Current Marijuana Use: Testing the Mediating Role of Marijuana-Use Coping Motives Among Active Users

Abstract: ABSTRACT. Objective: The present investigation examined anxious arousal and anhedonic depression symptoms in relation to frequency of past-30-day marijuana use, as well as the role of marijuana-use coping motives in terms of mediating this relation. Method: The present sample included current young adult marijuana users (N = 154; 48.1% female; mean [SD] age = 20.75 [5.97] years) who were recruited via study fl yers and printed advertisements in local newspapers placed throughout the Burlington, VT, community. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 42 publications
2
19
2
Order By: Relevance
“…Indeed, other studies have demonstrated associations between anhedonia and use of other drugs, including cocaine and amphetamine ( Leventhal et al, 2008( Leventhal et al, , 2010, cannabis ( BonnMiller, Zvolensky, Marshall, & Bernstein, 2007 ;Dorard, Berthoz, Phan, Corcos, & Bungener, 2008 ;Dumas et al, 2002 ;Johnson, Bonn-Miller, Leyro, & Zvolensky, 2009 ), and opiates ( Zijlstra, Veltman, Booij, van den Brink, & Franken, 2009 ). Regardless of whether low hedonic capacity may confer risk to other drugs of abuse, the current study suggests that this trait may be an important variable to identify youth at risk for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other studies have demonstrated associations between anhedonia and use of other drugs, including cocaine and amphetamine ( Leventhal et al, 2008( Leventhal et al, , 2010, cannabis ( BonnMiller, Zvolensky, Marshall, & Bernstein, 2007 ;Dorard, Berthoz, Phan, Corcos, & Bungener, 2008 ;Dumas et al, 2002 ;Johnson, Bonn-Miller, Leyro, & Zvolensky, 2009 ), and opiates ( Zijlstra, Veltman, Booij, van den Brink, & Franken, 2009 ). Regardless of whether low hedonic capacity may confer risk to other drugs of abuse, the current study suggests that this trait may be an important variable to identify youth at risk for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on negative affect associated with use has focused on anxiety, with evidence for the effect of anxiety on marijuana use being mediated by tension-reduction expectancies (de Dios et al, 2010) and coping motives for use (Johnson et al, 2009). EMA research with young, frequent marijuana users has suggested that the association between anxiety and subsequent marijuana use may be mediated by the effects of anxiety on craving (Buckner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…(Predictions from CB-TRT studies are also supported for marijuana use; Johnson et al, 2009). Findings showing that those with alcohol problems are more likely than others to expect tension reduction from alcohol and to drink to obtain these effects add face validity to the CB-TRT as a psychosocial model for the etiology of alcohol dependence (Beckman, 1980;Carpenter and Hasin, 1999;Russell and Bond, 1980).…”
Section: The Cognitive-behavioral Tension-reduction Theory (Cb-trt)mentioning
confidence: 92%